Clinical practice guideline for chronic headache 2013. Issue 5 (22nd August 2019) - Araki, Nobuo; Takeshima, Takao; Ando, Naoki; Iizuka, Takahiro; Igarashi, Hisaka; Ikeda, Yukio; Ito, Yasuo; Inagaki, Mieko; Imamura, Keiko; Ohkuma, Hirohisa; Ogawa, Karin; Kato, Yuji; et al.
Abstract: International Headache Society published the International Classification of Headache Disorders 2nd Edition (ICHD‐II) in 2004. In response to this development, the "Clinical Practice Guideline for Chronic Headache" was compiled in Japan by the Study Group for Chronic Headache Clinical Practice Guideline Development. In 2006, the book entitled "The Clinical Practice Guideline for Chronic Headache (edited by Japanese Headache Society)" was published as the first edition. As triptans have become widely used, clinical practice for chronic headache has also been changed in Japan and there was a need to revise the first edition. Essentially based on the first edition, the new guideline has added the latest information and presented the concept of international standards of chronic headache care. This guideline included eight chapters and appendix: I. headache: general considerations, II. migraine, III. tension‐type headache, IV. trigeminal autonomic cephalalgias, V. other primary headache disorders, VI. medication‐overuse headache, VII. headaches in children, and VIII. genetics. We have published the second version in Japanese in 2013, but 1 month after we published the original guideline, the International Classification of Headache Disorders 3rd Edition beta version (ICHD‐3beta) was published. We changed this guideline to the new version in English based on ICHD‐3beta. This guideline is the final product of the Committee's efforts in 2015, which was opened in the home page of the Japanese Headache Society. This manuscript was written to show the main part of this guideline as Recommendation of each CQ. Among 121 CQs, only five CQ was selected to present full sentences including not only Recommendation but also other parts.